Deep transcranial magnetic stimulation for obsessive compulsive disorder. (2nd October 2020) - McCathern, Alexis G.; Mathai, David S.; Cho, Raymond Y.; Goodman, Wayne K.; Storch, Eric A.
ABSTRACT: Introduction: Obsessive-compulsive disorder (OCD) is a common psychiatric disorder that can be chronic and debilitating if not properly treated. Current first-line treatments for OCD include cognitive-behavioral therapy with exposure and response prevention and serotonin uptake inhibitor medications; however, these therapies are not effective for all individuals. Areas covered: Deep transcranial magnetic stimulation (dTMS) has been hypothesized to be an effective alternative for individuals with treatment-resistant OCD. dTMS has thought to be favorable due to its low side effect profile and its minimally invasive nature. Expert opinion: This review evaluates the current research on effectiveness of dTMS therapy for individuals with treatment-resistant OCD. This review also investigates shortcomings in current dTMS research and the hypothesized future of dTMS therapy.